Development and validation of a novel triplex droplet digital PCR assay for simultaneous detection of African swine fever virus, pseudorabies virus, and porcine parvovirus - Yu, Jiarong; Zhu, Lu; Zuo, Yuanyuan; Gao, Shengbin; Wang, Qinghua; Xu, Jiao; Fang, Linlin; Liu, Yumeng; Liu, Shuang; Wang, Xiaozhen; Wang, Xiaohua; Wang, Yingli; et al. (Frontiers in Microbiology, 2026)
Coinfection with multiple viruses significantly complicates swine disease management. DNA viruses including African swine fever virus (ASFV), pseudorabies virus (PRV), and porcine parvovirus (PPV) are causing reproductive failure in sows, with overlapping clinical presentations that challenge differential diagnosis. To address this, we developed a novel triplex droplet digital PCR (ddPCR) assay using three distinct fluorescent probe sets for simultaneous detection of these three viruses. The multiplex ddPCR demonstrated superior analytical performance with high specificity, sensitivity, and reproducibility. When compared to conventional quantitative PCR (qPCR), the ddPCR assay achieved limits of detection (LOD) of 0.08, 3.41, and 3.38 copies/μL for ASFV, PRV, and PPV respectively-representing approximately 10-fold lower LOD values than corresponding qPCR methods. Cross-reactivity tests confirmed absolute specificity against other important swine pathogens. Clinical validation using 217 field samples revealed marked diagnostic advantages: ddPCR detected positive cases in 137 samples (63.1%) versus 115 (53.0%) by qPCR. Species-specific positivity rates showed ddPCR improved detection by 5.99% (ASFV), 0.46% (PRV), and 3.69% (PPV) compared to qPCR. Concordance analysis demonstrated strong agreement between methods (94.01–99.54%), with ddPCR showing superior sensitivity particularly for low-viral-load samples. This study establishes the first multiplex digital PCR platform for simultaneous differential diagnosis of ASFV, PRV, and PPV. The assay provides a robust tool for enhanced surveillance and control of these economically significant pathogens in swine populations.